Manufacturing of Crystal Palm Sugar and Digital Product Marketing in Lubuk Bendahara Timur Village - Said Zul Amraini; Zuchra Helwani; Muhammad Mardhiansyah; Warman Fatra; Reno Susanto (Yayasan Literasi Sains Indonesia, 2022)
Palm sugar agro-industry in Rokan Hulu Regency has obstacles in its development, namely technological capabilities, and limited supporting infrastructure for agro-industry, marketing and distribution that are less developed. The purpose of this service is to design a tool to make crystal sugar so that it can convert solid palm sugar which is usually produced by the community so that the price of palm sugar is higher than ordinary solid palm sugar and assist in digital marketing. This community service method is carried out in several stages, namely: observation, problem identification, problem formulation and finding the best solution. Through this service program, this service, the University of Riau implementation team has succeeded in designing and manufacturing palm sugar crystallization tools, socializing the use of the tool, counseling about digital marketing, and counseling efforts to change people's mindsets in the behavior of using sap water as an ingredient for making palm sugar.